Working with mentally handicapped people : different layers of intra-personal and inter personal experience - Zissis, Chrisostomos (Department of Psychology, 2024)
In a care to develop ideas of how a better understanding of resources is rPo-nrPr"' who provide the care a so as to can help improve provision for people with a mental handicap. The case study focuses on the subjective experiences of professional caregivers while working in a non-governmental organisation which provided protective employment to mentally handicapped adults. The participants who were employed as staff a group protective v,rorkshops, participated in once weekly staff groups, which were facilitated by two intern clinical psychologists. Their accounts and experiences were noted and analysed using a body of theory, which informs a psychoanalytic understanding of mental handicap and views group phenomena as having a close correspondence to the psychological and dynamic processes of individuals. 'fhe case material illustrates that in certain instances the dynamics and of a staff group, and the internal experiences professional caregivers seemed to parallel those of their mentally handicapped clients. addition to expressing and responding to certain emotional experiences that literature notes may be stirred up inside mentally handicapped people and their parents, it seemed that the staff relied on certain protective mechanisms in an attempt to contain their difficult feelings while working with mentally handicapped adults. It is argued that a clearer understanding of the emotional experiences of professional caregivers in relation to their colleagues and mentally handicapped may be usef.ll in improving the service provision for mentally handicapped people, as well as ensuring that professional caregivers are adequately supported their work.